Association of genetic variants with myocardial infarction in Japanese individuals with chronic kidney disease - Fujimaki, Tetsuo; Kato, Kimihiko; Yoshida, Tetsuro; Oguri, Mitsutoshi; Watanabe, Sachiro; Metoki, Norifumi; Yoshida, Hidemi; Satoh, Kei; Aoyagi, Yukitoshi; Nishigaki, Yutaka; Tanaka, Masashi; Nozawa, Yoshinori; Kimura, Genjiro; Yamada, Yoshiji (Thrombosis and Haemostasis, 2009)
Chronic kidney disease (CKD) is a serious clinical condition that is associated with a high incidence of cardiovascular disease and end-stage renal disease. Although CKD has been recognised as a risk factor for myocardial infarction (MI), genetic factors for predisposition to MI in individuals with CKD have remained largely unknown. The purpose of the present study was to identify genetic variants that confer susceptibility to MI in Japanese individuals with CKD. The study subjects comprised 1,339 Japanese individuals with CKD, including 496 subjects with MI and 843 controls. The genotypes for 248 polymorphisms of 181 candidate genes were determined by a method that combines the polymerase chain reaction and sequence-specific oligonucleotide probes with suspension array technology. An initial screen of allele frequencies by the chi-square test revealed that the 11496G→A (Arg353Gln) polymorphism of F7 (rs6046) was significantly (false discovery rate <0.05) associated with the prevalence of MI in individuals with CKD. Subsequent multivariable logistic regression analysis with adjustment for covariates and a stepwise forward selection procedure also revealed that this polymorphism was significantly (p <0.005) associated with MI, with the variant A (Gln) allele protecting against this condition. Determination of genotype for the 11496G→A (Arg353Gln) polymorphism of F7 may prove informative for assessment of the genetic risk for MI in individuals with CKD.
Keywords: Chronic kidney disease; genetics; myocardial infarction; polymorphism